Determination of Farming Business Insurance Premium Prices with the Variance Premium Principle and Standard Deviation Premium Principle Methods - Pramujati, Windya Harieska (Operations Research: International Conference Series, 2021)
The agricultural sector is one of the most important economic sectors in Indonesia, however, agricultural business can also pose a risk of loss resulting in a decrease in agricultural production. This is caused by several factors such as plant pests, weeds, and rainfall. Therefore it is necessary to make an effort to reduce the risk of losses that occur, one of which is by implementing an insurance policy. The risk experienced by farmers is assumed to be a random variable that has a certain distribution. So that the calculation of this risk is related to the probability model, one of which is the aggregate loss model. Then applied the principle of variance premium, and standard deviation premium to calculate the amount of insurance premiums. The amount of premium generated for each of these principles is 2,396,277 and 2,012,839. So it can be said that with the same risk, the standard deviation premium principle produces a premium price that is more economical than the variance premium principle. So that if this principle is applied, farmers will benefit more if they insure their agricultural businesses.